2022
DOI: 10.1515/biol-2022-0062
|View full text |Cite
|
Sign up to set email alerts
|

Endostar plus pembrolizumab combined with a platinum-based dual chemotherapy regime for advanced pulmonary large-cell neuroendocrine carcinoma as a first-line treatment: A case report

Abstract: Pulmonary large-cell neuroendocrine carcinoma (LCNEC) is a rare and highly aggressive cancer with a very poor prognosis. The proper treatment decision and possible prognosis outcome for advanced LCNEC is always an enormous challenge due to its scarcity. Here, we presented a 59-year-old male patient with advanced LCNEC with a non-neuroendocrine immunophenotype who received endostar plus pembrolizumab combined with a platinum-based dual chemotherapy regime as a first-line treatment. At present, the patient’s con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Furthermore, Oda et al ( 59 ) reported a case of obtaining complete response (CR) for up to 4°years after treatment with pembrolizumab. According to the report of Zhang et al ( 60 ), pembrolizumab plus endostar was administered as first-line therapy for a patient diagnosed with LCNEC, the PFS was 2°years. Sherman et al ( 61 ) conducted a clinical trial in which a total of 37 patients with advanced LCNEC were enrolled, patients ( n = 21) who received anti-PD-1/PD-L1 immunotherapy demonstrated an ORR of 33%, a complete response rate (CRR) of 11%, a mPFS of 4.2°months (95% CI, 2.4−8.1), and a mOS of approximately 11.8°months (95% CI, 3.7-NR).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Oda et al ( 59 ) reported a case of obtaining complete response (CR) for up to 4°years after treatment with pembrolizumab. According to the report of Zhang et al ( 60 ), pembrolizumab plus endostar was administered as first-line therapy for a patient diagnosed with LCNEC, the PFS was 2°years. Sherman et al ( 61 ) conducted a clinical trial in which a total of 37 patients with advanced LCNEC were enrolled, patients ( n = 21) who received anti-PD-1/PD-L1 immunotherapy demonstrated an ORR of 33%, a complete response rate (CRR) of 11%, a mPFS of 4.2°months (95% CI, 2.4−8.1), and a mOS of approximately 11.8°months (95% CI, 3.7-NR).…”
Section: Treatmentmentioning
confidence: 99%
“…The 12-month survival rate was 34.0% versus 24.1%, while the 18-month survival rate stood at 29.1% versus 15.0% in the patients treated with or without immunotherapy. Furthermore, Oda et al (59) reported a case of obtaining complete response (CR) for up to 4 • years after treatment with pembrolizumab. According to the report of Zhang et al (60), pembrolizumab plus endostar was administered as first-line therapy for a patient diagnosed with LCNEC, the PFS was 2 • years.…”
Section: Immunotherapymentioning
confidence: 99%